PSYCHOLOGICAL POTENTIAL OF SCHOOL GRADUATES IN CHOOSING A PROFFESSION OF MARKET ECONOMY - Honchar, Anatolii (Continuing Professional Education: Theory and Practice, 2019)
The article is devoted to the characteristics of the psychological capacity of the secondary school graduates that promotes the selection of the market trade. The principles of the integrity in choosing of entrepreneur professions are analyzed. The concept of the effective actions that can be called a business activity is observed as the central to the understanding of entrepreneurship